Slavery and the Making of America - Horton, James Oliver and Horton, Lois E. (Oxford Oxford University Press, 2006)
Paperback edition of the companion to the four-part PBS series on the history of American slavery which aired February 2005.
Include Index and Notes and Illustration
Keywords: Slavery -- United States -- African Americans